ORGANOCHLORINE PESTICIDES AND POLYCHLORINATED BIPHENYLS (PCBS) IN SEDIMENTS AND BIOTA FROM FOUR US ARCTIC LAKES - Susan Allen-Gil; C Gubala; ROBERT WILSON; DIXON LANDERS; T Wade; J Sericano; L Curtis (ARCHIVES OF ENVIRONMENTAL CONTAMINATION AND TOXICOLOGY V. 33(4): 378-387 SPRINGER-VERLAG NEW YORK INC, 2005)
Organochlorine (OC) concentrations in surface sediment, snails (Lymnea sp.), and two freshwater fish species (grayling, Thymallus arcticus; and lake trout, Salvelinus namaycush) from four lakes in the US Arctic were determined. In surface sediment, chlorinated benzenes (including hexachlorobenzene, HCB),and p,p'-DDT were the primary analytes detected (max = 0.7 ng/g dry wt), while individual polychlorinated biphenyl (PCB) congeners were always below 0.1 ng/g. A wider range of compounds and higher concentrations were found in lake trout, the top predatory fish species in the same lakes. The concentration ranges for hexachlorocyclohexanes (HCHs), chlordane-related compounds (CHLORs), DDTs, and PCBs in lake trout and grayling were similar to those reported for other arctic freshwater fish (1-100 ng/g wer wt), but one to two orders of magnitude lower than Great Lakes salmonids. Nitrogen isotope analysis confirmed that differences in OC concentrations between grayling and lake trout are explained partly by differences in food web position.